Autologous vascular proximal fibular graft in the treatment of giant cell tumor of the distal radius-a case report - Todorova, Teodora; Gramatnikovski, Nikola; Angelovska, Tamara; Kostadinova Kunovska, Slavica; Manevska, Nevena; Foteva, Marta; Samardjiski, Milan (Oxford University Press and JSCR Publishing Ltd., 2024)
Giant cell tumor of bone (GCTB) represents an intermediate, locally aggressive tumor, with a peak of incidence in the third decade of life with female predominance (2:1). The distal radius is the third most common localization and especially challenging in the treatment is saving the wrist joint function. In this report, we present a case of a 32-year-old patient diagnosed with a giant cell tumor of the distal radius, primarily treated with curettage of the bone. Due to aggressive tumor recurrence, considering local control of the tumor, we decided to perform a resection of the distal radius and reconstruction with an autologous proximal vascular fibular graft. We performed a SPECT/CT scan to confirm the functionality of the graft. We find this procedure a safe technique for local control of tumor recurrence and an ideal substitute for a limb salvage procedure.
Keywords: bone scan; autologous proximal fibular vascular graft; distal radius